Genetic variability, heritability and character association of grain yield and its components among selected genotypes of maize (Zea mays L.), Gezira State, Sudan - Hersi, Ali A.M.; Ibrahim, Abu Elhassan S.; Suliman, Suliman H.; Suliman, Abbas M. (Gezira Journal of Agricultural Science, 2019)
In the Sudan, the low yield of maize was mainly due to the use of low yielding land races and open-pollinated varieties. Hence, the current study was conducted to measure the extent of genotypic and phenotypic variability, genotypic performance, heritability, genotype x season interaction, and the magnitude of association among seed yield and its components of 10 maize genotypes. The experiment was carried out during the summer of 2017 and the winter of 2017/18, using a randomized complete block  design with three replicates, at the University of Gezira Farm, Wad Medani, Sudan. The characters measured were days to 50% tasseling and silking, plant and ear height, number of kernels per row and per ear, ear diameter, cob length, 100-kernels weight and grain yield. High significant phenotypic variability was detected for all the measured characters. Seasonal differences were also significant. High broad sense heritability estimates were recorded for 50% tasseling and silking and plant height while the rest of the characters showed moderate estimates. The study confirmed the fact that maize is a summer crop in central Sudan. In summer, the highest seed yield genotype was HSD 5158 (2609 kg/ha) and in winter was HSD 3538 (2285 kg/ha). Days to 50% tasseling and silking and plant height were significantly and positively correlated with yield and so recommended as selection criteria for seed yield improvement. It is recommended to grow genotypes HSD 5158 in summer and HSD 3538 in winter as well as genotypes VMH 4040, VMH 4102 and HSD 5007 in both seasons. Testing of these genotypes under different locations and seasons is suggested.              يعزى ضعف إنتاجية الذرة الشامية بالسودان لزراعة أصناف مفتوحة التلقيح وسلالات محلية ضعيفة الإنتاج. هدفت هذه الدراسة لقياس التباين الظاهري والوراثي ودرجة التوريث على المدى العريض وتفاعل الطراز الوراثي والموسم وارتباط إنتاج البذور ومكوناته. نفذت التجربة في صيف 2017 وشتاء 18/2017 بتصميم القطاعات العشوائية الكاملة بثلاث مكررات بمزرعة جامعة الجزيرة، واد مدني، السودان. الصفات التي  قيست هي : عدد الأيام لظهور 50% من الأزهار المذكرة والمؤنثة وطول النبات وارتفاع القندول وعدد بذور الصف والقندول ومحيط القندول وطول الكوز ووزن مائة حبة وإنتاج البذور. أظهرت النتائج اختلافاً معنوياً بين الطرز الوراثية لكل الصفات وفي الموسمين. تأثير الموسم كان معنوياً. سجلت قيم عالية لدرجة التوريث بالمعنى العريض لصفات 50% إزهار مذكر ومؤنث وطول النبات ولكن الصفات الأخرى أظهرت قيم وسطية. ثبت أن محصول الذرة الشامية في وسط السودان محصول صيفي. الطراز الذي أعطى أعلى إنتاجية صيفاً هو HSD 5158 (2609 كجم/هـ) وشتاءً  هو  HSD 3538 (2285 كجم/هـ). ارتبطت صفات الإزهار المؤنث والمذكر وطول النبات ارتباطاً موجباً ومعنوياً بالإنتاجية وعليه يمكن استعمالها كمؤشرات انتخاب لتحسين إنتاجية الحبوب. يوصى بزراعة الطراز HSD 5158  صيفاً والطراز HSD 3538 شتاءً والطرز VMH 4040 و VMH 4102 و HSD 5007 في الموسمين معاً. يوصى بزراعة هذه الطرز المقترحة في مواسم ومواقع متعددة لتأكيد النتائج.